Efficiency Improvement, Design Optimization, and Expansion of Oxygen Flow Valve Holes in Small Industrial Scale Husk Furnaces - Hanifan, Rahmah Asri Nurani; Hajar, Siti; Har, Nazopatul Patonah; Zuhri, Mahfuddin; Rustami, Erus; Nikmatin, Siti; Irzaman, Irzaman (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2023)
Indonesia has an abundant amount of industry. Production in large, medium, and small industries still uses gas and oil as fuel sources. The fuel sources used still come from non-renewable energy. There is a need for alternative use of renewable energy to reduce the use of non-renewable energy. One solution is the use of rice husk biomass as a fuel source. Rice husk is still often considered as waste despite its many utilizations. The utilization of rice husk waste must be improved to increase its beneficial value. Rice husk waste can be utilized as a fuel source in a husk furnace. A husk furnace is a cooking device in which the fuel (rice husk) is burned using direct combustion. This research aims to optimize the efficiency of the husk furnace by varying the size of the oxygen flow valve hole and the mass of water being heated. Tests were conducted on four variations of oxygen flow valve hole size, namely, 36x27 cm2, 36x34 cm2, 43x34 cm2, and 50x34 cm2, and two variations of water mass (6 and 18 kg). The research was conducted by heating water using the Water Boiling Test method with test parameters: heating time, fuel consumption rate, energy in, energy out, heat efficiency, heat transfer rate, and ash and charcoal yield. The significant efficiency value can be used as a reference for small-scale industrial rice husk furnaces. The most significant efficiency in the study was 54.99%, achieved by a 43x34 cm2 valve hole for heating 18 kg of water. Based on the most effective efficiency value gained, the expansion of the oxygen flow valve hole is sufficient to be used as a test parameter to test the optimization of small industrial-scale husk furnaces.